Evaluating the impact of metabolic syndrome on postoperative thyroidectomy outcomes. Issue 4 (28th December 2020) - Elsamna, Samer T.; Suri, Pooja; Mir, Ghayoour S.; Roden, Dylan F.; Paskhover, Boris
Abstract: Objective: Metabolic syndrome (MetS) has previously been linked to increased risk of postoperative morbidity and mortality in other surgical undertakings. Because MetS is a consequence of endocrine dysfunction, and given the thyroid's crucial role in endocrine homeostasis, we sought to evaluate the association between MetS and postoperative outcomes of thyroidectomy. Methods: Data were acquired from the ACS‐NSQIP database from years 2005 to 2017. Patients with obesity, diabetes, and hypertension were defined as having MetS. Odds ratios (OR) were obtained for outcomes to quantify risk with multivariate logistic regression. Results: Outcomes significantly affected by MetS included overall complication (OR: 2.00), extended postoperative stay (OR: 1.52), medical complication (OR: 1.48), surgical complication (OR: 1.62), and mortality (OR: 2.33). Conclusions: Patients with MetS undergoing thyroidectomy are at increased risk of an increased length of stay, overall complications, and mortality.